صعوبات تعلم مهارة التحدث باللغة العربية، دراسة مقارنة بين طلاب آتشيه وجايو - Abdullah, Maulidati; Yacob, Maimun M. (STAINI Press, 2025)
IAIN Takengon is one of the campuses that has multicultural students, among them Gayo, Acehnese, etc. In learning Arabic, the researcher acts as a lecturer. Found various difficulties faced by students. Among them are problems in speaking Arabic which are influenced by the student's mother tongue. So here, the researcher is encouraged to discuss student's difficulties in speaking Arabic. Especially in the Gayo and Acehnese tribes, because the majority of students come from the Gayo tribe, followed by the Acehnese tribe. This study aims to see the difficulties faced by two groups of students who are learning Arabic conversation, namely Gayo and Acehnese student groups, this study uses a comparative method, and the research tools used are observation, questionnaires, and documentation, this study was conducted at IAIN Takengon, Arabic language education and Islamic economics study program with 31 students. The results of the study showed that there were 2 problems faced by Acehnese and Gayo students in speaking Arabic, first: general problems which include not memorizing vocabulary, feeling embarrassed when speaking in front of friends, being afraid of making mistakes in pronunciation, lack of opportunities to practice Arabic in the college environment, not understanding grammar and morphology rules, having no previous language experience and not matching the language of the book with the regional language. The specific problem is that both groups of students, namely Acehnese and Gayo, have difficulty speaking Arabic. The habit of thinking in another language (mother tongue), is influenced by the structure of the mother tongue, and difficulty in adapting some letters of the alphabet, the next problem is that the intonation in Acehnese is very strong so it continues when speaking Arabic, while the intonation in Gayo has no real influence on speaking Arabic.